The Effect of Lavender Aromatherapy on The Quality of Sleep Among Patients with Type 2 Diabetes Mellitus - Azhar, Bayu; Serizka, Shahaila Refa; Arfina, Angga; Putra, Ifon Driposwana (Universitas Fort De Kock Bukittinggi, 2025)
Background: Insulin resistance in the pancreas is a characteristic of diabetes mellitus, a chronic metabolic and inflammatory disease. People with diabetes mellitus may experience foot pain and tingling at night, which are common symptoms. The main components in lavender aromatherapy, especially linalool acetate, can improve sleep quality. This research aims to find out how lavender aromatherapy affects the sleep quality of individuals with type 2 diabetes.Methods: With a quasi-experimental design and pre and post test procedures in one group without controls, the methodology used is quantitative. Purposive sampling was used to select 19 respondents suffering from type 2 diabetes mellitus in the Payung Sekaki Health Center Work Area, Pekanbaru City. Data was collected and the respondents' sleep quality was evaluated using a diffuser and lavender essential oil using the Pittsburgh Sleep Quality Index (PSQI) questionnaire. For five days, the intervention was carried out every night thirty minutes before bedtime. Paired T Test was used for bivariate data analysis. Results: The average sleep quality score of respondents was 13.05 with a standard deviation of 2.46 before the intervention, and 4.78 with a standard deviation of 1.31 after the intervention. Results showed by a statistical analysis p value of 0.000 which shows that the use of lavender aromatherapy greatly improves the sleep quality of people with type II diabetes mellitus. Conclusion: Research participants learned about the benefits of lavender aromatherapy to improve sleep quality for people with type 2 diabetes.